Adapting to the new frontier: the evolution of international sports law in the digital age - Jady Zaidi Hassim,; Mohamad Izzat Amyar Mohamad Arif,; Athirah Mohd Anuar,; Aminurasyed Mahpop, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The dynamic changes occurring in international sports law due to the transformative influence of the digital era require adjusting to the new landscape of sports law. This article examines how the digital era has reshaped various aspects of the sports industry, from broadcasting rights and fan engagement to data protection, sports betting, and the recognition of emerging sports like esports. It delves into the challenges and opportunities that arise from these changes and highlights the need for international sports law to adapt and evolve. The article analyses the shifting landscape of sports broadcasting, where online streaming platforms have disrupted traditional models and necessitated the development of new legal frameworks to address piracy and protect intellectual property rights. It also explores the rise of social media and the challenges it poses in terms of privacy, defamation, and athlete endorsement. Furthermore, the article discusses the implications of data collection and the need for robust regulations to ensure the privacy and security of athletes' personal information. It explores the expansion of online sports betting and the measures taken to combat match-fixing and corruption, as well as the recognition of esports as a legitimate sporting activity and the legal considerations it entails. By examining the evolution of international sports law in the digital age, this article provides valuable insights into the complex interplay between technology, regulation, and the preservation of the integrity and fairness of sports.